Seren Taun Tradition in Cibadak Lebak Banten During Pandemic - Erusmiati Erusmiati; Busro Busro (UIN Sunan Gunung Djati Bandung, 2022)
Seren taun is a ceremonial tradition of celebrating their harvest, the seren taun tradition or this seren taun ceremony is an event that must be carried out by every indigenous community that aims to thank God for the harvest they get. Examine the changes that occur during a pandemic. The object of this research is a kasepuhan community, the kasepuhan community is an indigenous people who believe by implementing seren taun will strengthen togetherness and solidarity that exists in society. The Kasepuhan community was chosen because in this community they can maintain and preserve what their ancestors had built in ancient times, one of which is the Seren Taun tradition which is always carried out every year from the past until now as a thank you to God for providing abundant rice harvests and Pray that next year the results will be more abundant than before. This research method was conducted by interviewing a resource person who is the grandson of the traditional chairman of Kasepuhan in Citorek Village, Lebak Regency, Banten Province, which plays an important role when the Seren Taun ceremony takes place. This research also uses library research and observation methods by collecting various data and information such as through various documents, either in writing or by taking photos or pictures. With the interview and observation method, of course, the researchers examined the seren taun in the village of Cibadak, Lebak Regency, Banten. It turns out that the people in Cibadak village, which are customary communities in Lebak Regency, have traditions that are still maintained today, in fact nothing has changed from this tradition, the seren taun tradition is a culture that has been preserved until now. Because even though times have developed and there are many advanced technologies in this modern era, the Cibdak people of Lebak Regency still hold fast to their belief in their ancestors who have brought Seren Taun and still preserve the culture that has been built for a long time so that Seren Taun is maintained until now.